(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Introduzione - 2. La libertà di espressione e la libertà di coscienza - 3. Le tematiche bioetiche - 4. I simboli e l’identità - 5. Considerazioni conclusive. Religious minorities in Italy. New problems (?) ABSTRACT: In the contest of a wider pluralism of the Italian society, legislation still struggles to guarantee an real equal treatment to all religious minorities. Religious denominations - who ratified an intesa with the Government - are for sure in a privileged position compared to those who are still regulated by the general law. Among the last ones, the Italian jurisprudence is playing an important role to find a balance especially on those issues that ask for a more decise government of religious diversity.